Pengaruh Net Profit Margin, Debt To Equity Ratio, Return On Equity Dan Dividend Payout Ratio Terhadap Harga Saham - Marlina, Rini (CV. ITTC INDONESIA, 2024)
This study aims to examine and analyze the effect of Net Profit Margin, Debt to Equity Ratio, Return On Equity and Dividend Payout Ratio on stock prices. So the research design used is causal research. The population of this research is all companies in the Infrastructure, Utilities and Transportation Sector Services Listed on the Indonesia Stock Exchange for the 2018-2020 period as many as 71 companies. The sample was taken by non-probability method with purposive sampling technique and obtained a sample of 12 companies that meet the criteria. The research data was taken from the financial statements and annual reports of each sample company, which was obtained from the official website of the Indonesia Stock Exchange, namely https://www.idx.co.id. The data was processed using SPSS with multiple linear regression method. Based on the tests that have been carried out, the results obtained that partially Net Profit margin and Dividend Payout Ratio have a positive effect on stock prices, while Debt to Equity Ratio and Return On Equity have no effect on stock prices.